The transpiration rate sensitivity to increasing evaporative demand differs between soil textures, even in wet soil - Koehler, Tina; Botezatu, Ákos; Murugesan, Tharanya; Kaliamoorthy, Sivasakthi; Kholová, Jana; Sadok, Walid; Ahmed, Mutez Ali; Carminati, Andrea (Plant stress (Amsterdam), 2024)
•Transpiration regulation during rising VPD is soil texture-specific even in wet soil.•Leaf area and root:shoot-ratio do not consistently differ between soils.•Maximum canopy conductance scales with soil hydraulic conductivity in the wet range.•Plants limit transpiration at lower VPD when their maximum canopy conductance is high. Many efforts to improve crop yields in water-limited environments have been directed towards identifying genotypes capable of restricting their transpiration rate (TR) at high vapor pressure deficit (VPD). This has proven challenging due to the dependence of the TR-VPD relationship on environmental conditions. In this context, however, the impact of edaphic properties on the TR response to VPD has largely been overlooked as experiments investigating the TR-VPD relationship are usually performed in wet soil conditions. Hence, the soil is not expected to be limiting the water supply to the canopy at high VPD. Nonetheless, soil (hydraulic) properties are known to shape plant growth and the development of the plant hydraulic system. Thereby, they might indirectly affect plant water use during rising VPD, even in wet soils. To test the soil dependency of the TR-VPD relation, we measured the TR response of genotypes of three important C4 cereals - maize, sorghum, and pearl millet - to increasing VPD in two soil textural classes (sandy loam vs. clay loam). We show that the TR response to rising VPD differed among soil textures in wet conditions. Plants grown in sandy loam exhibited a higher initial slope in TR during increasing VPD (slope1), a restriction in TR at lower VPD (VPDBP), and a greater difference in TR before and after the VPDBP (slopediff.), compared to plants grown in clay loam. Additionally, plants grown in more conductive soils (i.e., sandy loam) systematically exhibited higher maximum canopy conductance (i.e., slope1) and restricted their transpiration rate at lower VPD levels (VPDBP), resulting in a greater reduction in transpiration. This aligns with a hydraulic mechanism underpinning TR response to VPD. We advocate that considering soil texture is valuable in breeding for water conservation based on TR restriction under increasing VPD.